A Review of Antimicrobial Activity of Dental Mesenchymal Stromal Cells: Is There Any Potential? - Andrukhov, Oleh; Blufstein, Alice; Behm, Christian (Frontiers in Oral Health, 2022)
Antimicrobial defense is an essential component of host-microbial homeostasis and contributes substantially to oral health maintenance. Dental mesenchymal stromal cells (MSCs) possess multilineage differentiation potential, immunomodulatory properties and play an important role in various processes like regeneration and disease progression. Recent studies show that dental MSCs might also be involved in antibacterial defense. This occurs by producing antimicrobial peptides or attracting professional phagocytic immune cells and modulating their activity. The production of antimicrobial peptides and immunomodulatory abilities of dental MSCs are enhanced by an inflammatory environment and influenced by vitamin D3. Antimicrobial peptides also have anti-inflammatory effects in dental MSCs and improve their differentiation potential. Augmentation of antibacterial efficiency of dental MSCs could broaden their clinical application in dentistry.